Digital Сompetence of Russian School Teachers - Soldatova, G.U.; Shlyapnikov, V.N. (Psihologičeskaâ nauka i obrazovanie, 2015)
This article presents the results of digital competence study in different types of pedagogical stuff of Russian educational organization (informatics teachers – 140 participants, subject teachers – 145 participants, other categories – 112 participants) in comparison to the results of all-Russia digital competency study among schoolchildren and parents (2013). We use Index of Digital Competency to as¬sess the digital competence of schoolteachers. The results shows that schoolteachers significantly exceed schoolchildren and parents in digital competency (F(2)=32,03, p<0,001), in frequency of internet-usage ( χ2(14)= 597,61, p<0,001), in time spent in the Internet everyday ( χ2(14)=472,83, p<0,001). Also they prefer other types of devices for internet-activities. Informatics teachers significantly exceed other teachers in digital competency (F(2)=14,18, p<0,001). These results let make the conclusion that modern schoolteachers are able and ready to improve their pupils’ digital competency by means of different ICT. Представлены результаты исследования цифровой компетентности педагогических работников разной категории (учителей информатики – 140 человек, учителей предметников – 145 человек, других категорий – 112 человек) российских образовательных организаций в сравнении с данными Всероссийского исследования цифровой компетентности подростков и родителей (2013). Для оценки уровня цифровой компетентности учителей в работе была использована методика «Индекс цифровой компетентности». По¬лученные данные свидетельствуют о том, что учителя значимо превосходят школьников и родителей по уровню цифровой компетентности (F(2)=32,03, p<0,001), по частоте использования Интернета (χ2(14)= 597,61, p<0,001), по времени, проводимому в Интернете ежедневно (χ2(14)=472,83, p<0,001), а также отдают предпочтение другим устройствам для выхода в Интернет и видам деятельности в Сети. Показано, что по уровню цифровой компетентности учителя информатики значимо превосходят своих коллег (F(2)=14,18, p<0,001). Таким образом, современные учителя способны и готовы повышать цифровую компетентность своих учеников, используя для этого информационно-коммуникационные технологии.